KUALITAS PENGUNGKAPAN PELAPORAN IKLIM DENGAN REKOMENDASI TCFD PERUSAHAAN METAL-MINING DAN BANKS TAHUN 2020-2022 - Valentina Nusa Daton; Carmel Meiden (Bajang Institute, 2024)
Climate change has become a concern for every sector, including finance. This is the basis for the creation of the Task Force on Climate-Related Financial Disclosures (TCFD) recommendations. This research aims to determine the quality of climate reporting disclosure following TCFD recommendations. The theories employed in this study are stakeholder theory and legitimacy theory. The content analysis method is utilized to understand and assess the quality of climate reporting disclosure from 18 companies during the period 2020-2022. The results indicate that the majority of companies achieve a moderate quality, suggesting that the implementation of TCFD recommendations is still considered sufficient. The main category of governance and the sub-category of target usage receive the highest rankings, indicating that the disclosure in these categories and sub-categories aligns with TCFD recommendations. The banking sector attains high quality, even though its impact on climate change is not direct. South Africa obtains a high percentage, while the United Kingdom consistently experiences improvement each year.